Overexpression of Head date 1 gene (Hd1): an adaptation of antarctic hairgrass to guano input from Macronectes giganteus colonies of Antarctica (Research, Society and Development, 2022)
The Antarctic biodiversity, beyond the species composition, also comprises interactions between fauna and flora. M. giganteus, is one of the species that occupy the antarctic ice-free areas for reproduction. The moss Sanionia uncinata (Hedw.) Loeske and Deschampsia antarctica Desv. gress, common in Antarctica, with other species make up vast green formations  and is associated with breeding areas of seabirds. These sites are large deposits of guano, because a large amount of birds those gather in colonies. Due to this large supply of guano, the soil becomes a deposit of minerals, mainly of nitrogen available in the form of ammonium and nitrate. The problem is that not all plant species tolerate high quantities of these substances so different plant species show trends in the mechanisms of tolerance to stress by ammonium, which have been proven at the molecular level. The aim of this study was to investigate the influence of breeding colonies of seabirds on plant populations in the South Shetland Islands, Antarctica, from a molecular perspective. From the analysis of the collected samples, using the RNA-Seq and qRT-PCR approach was possible to identify a single gene differential and significantly expressed in D. antarctica. The LOC_Os06g16380 gene among the sampled treatments (control, 1m and 10m), showed higher expression coming 1m near breeding areas of M. giganteus. Our results suggest that Hd1 is associated with the plants stress related to guano input since that soil analysis demonstrated a higher concentration of mineral nitrogen available near of breeding areas of seabirds.